KINERJA PELAYANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KEPADA MASYARAKAT - Krishardianto, Bagoes Irawan; Santosa TH, Djoko; Subarno, Anton (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
The objectives of this research are to investigate: (1) the performance of the Population and Civil Registry Office at Karanganyar regency; (2) the factors influencing the performance of the Population and Civil Registry Office at Karanganyar regency; and (3) the efforts taken to improve the performance of the Population and Civil Registry Office at Karanganyar regency.This research used a single embedded case study with the qualitative method. The sources of the research were informants, locations, documents or archives. The samples of the research were taken by using the purposive sampling technique and the snowball sampling technique. The data of the research were gathered through in-depth interview, observation, and documentation and were then validated by using the data source and data gathering method triangulations. They were analyzed by using the interactive technique of analysis.The results of the research show that the performance of the Population and Civil Registry Office in extending services to the community in Karanganyar regency has not been optimal for the community feels less satisfied with the services in terms of the timeliness and comfort of services. Such a performance is due to the limited number of its employees and their low ability in the computerization system. The factors affecting the performance of the Population and Civil Registry Office at Karanganyar regency include (1) work motivation of the employees, (2) ability of the employees, and (3) facility and infrastructure. The efforts taken so as to improve the performance of the Population and Civil Registry Office at Karanganyar regency are, among others, highly motivating and encouraging the employees to perform better through punishment and reward system. The employees shall be given training on computerization system. The facility and infrastructure shall be added in terms of quantity and completeness. Keywords: Performance and services to community.